2021
DOI: 10.1111/ivb.12355
|View full text |Cite
|
Sign up to set email alerts
|

Hemocyte activation and nodule formation in the giant keyhole limpet, Megathura crenulata

Abstract: The giant keyhole limpet, Megathura crenulata, lives in rocky intertidal and subtidal environments along the Southern California coast, where it is exposed to viruses, bacteria, and other potential pathogens. We demonstrate that when exposed to bacteria or latex beads, hemocytes from specimens of M. crenulata in vivo and in vitro immediately become adhesive and form nodules. The rapid activation of hemocytes suggests a role for an array of recognition proteins, and inhibition of nodulation by the tripeptide Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Overall, TEM observations revealed that histological morphology of melanosome or melanocyte in mantle of C. gigas was like that observed in foot epithelium of the ablone H. tuberculate (Bravo Portela et al, 2012) and skin epithelium of keyhole limpet Megathura crenulate (Martin et al, 2021). Additionally, another structure of melanin was observed in the epithelium of mantle in H. tuberculate that melanin was arranged as spiral membranes (Nogal & García, 2015).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Overall, TEM observations revealed that histological morphology of melanosome or melanocyte in mantle of C. gigas was like that observed in foot epithelium of the ablone H. tuberculate (Bravo Portela et al, 2012) and skin epithelium of keyhole limpet Megathura crenulate (Martin et al, 2021). Additionally, another structure of melanin was observed in the epithelium of mantle in H. tuberculate that melanin was arranged as spiral membranes (Nogal & García, 2015).…”
Section: Discussionmentioning
confidence: 87%
“…In vertebrate, a large number of melanocytic markers have been investigated, among of these, TYR is a highly specific and sensitive marker for melanocytic differentiation (Ordóñez, 2014; Saliba & Bhawan, 2021). Nevertheless, to our knowledge, rare paper related to immunohistochemical makers of melanin in bivalve was published, because in previous studied cases, melanin granule was commonly identified using histochemistry staining (Bravo Portela et al, 2012; Han et al, 2022; Jiang et al, 2020; Martin et al, 2021; Nogal & García, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Pomacea canaliculata hemocytes, as those of some other gastropods ( 19 , 20 ), exhibit in vitro a notable tendency to approach toward one another, resulting in the formation of aggregates. This phenomenon appears to be a fundamental characteristic of hemocyte behavior in P. canaliculata , as evidenced by the formation of spheroidal hemocyte nodules in primary cultures ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nodular hemocyte formations are known to occur in the major clades of Protostomia (e.g., 66 69 ) and Deuterostomia (e.g., 70 ). A particular case among the latter are the nodules formed in the zebrafish larvae ( Danio rerio , Teleostei, Cyprinidae) in response to Mycobacterium marinum inoculation, because these nodules (usually called granulomas or tubercles in the context of tuberculosis studies) have received a particular attention as a model of mycobacterial pathogenesis ( 71 75 ).…”
Section: The Ampullariid Immune System From a Morpho-functional Persp...mentioning
confidence: 99%